Metal-organic framework-mediated multi-enzyme nanoparticles and applications thereof

By encapsulating glycogen debranching enzyme and glucose oxidase layer by layer in the metal-organic framework Mn-Fe-MOF, a multi-enzyme cascade catalytic system was constructed, which solved the problem of time-consuming and labor-intensive traditional α-amylase detection, and achieved highly sensitive enzyme activity detection, which is suitable for real-time monitoring in the brewing process.

CN122629040APending Publication Date: 2026-08-25KWEICHOW MOUTAI COMPANY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510210207.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

Existing methods for detecting α-amylase are time-consuming and labor-intensive, cannot be monitored in real time, and are easily affected by endogenous substances, resulting in inaccurate results. Therefore, a highly sensitive and practical analytical method is needed.

Method used

A multi-enzyme nanocomposite material, Agl@MFM@Gox@MFM, was designed to immobilize glycogen debranching enzyme Agl and glucose oxidase Gox in a metal-organic framework Mn-Fe-MOF through layer-by-layer encapsulation, thereby constructing a multi-enzyme cascade catalytic system. The enzyme activity was detected using the chromogenic reagent ABTS.

Benefits of technology

This method enables rapid and accurate detection of α-amylase activity, exhibiting high sensitivity and practicality. It allows for real-time monitoring of enzyme activity during the brewing process, reducing detection costs and improving accuracy and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122629040A_ABST
    Figure CN122629040A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of metal-organic framework mediated multi-enzyme nanoparticles and its application, especially the method for alpha-amylase detection. By detecting product absorbance, the quantitative detection of alpha-amylase activity is realized. According to the nature of MFM analog enzyme and its ability as natural enzyme carrier, Agl@MFM@Gox@MFM is prepared, compared with natural enzyme, the composite material has strong resistance, can successfully protect the activity of enzyme. Based on the cascade catalytic system of multi-enzyme nanoparticles Agl@MFM@Gox@MFM, a biosensor is first synthesized and established for detecting alpha-amylase, successfully combines chemical catalyst with natural enzyme, has wide detection linear range (5-500 U / L) while has excellent specificity to alpha-amylase. Benefited from the advantages of low cost, easy preparation and excellent stability, the colorimetric sensor has been successfully used to determine the activity of alpha-amylase in koji.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a multi-enzyme nanoparticle based on a metal-organic framework and its applications, particularly a method for the detection of α-amylase. The quantitative detection of α-amylase activity is achieved by measuring the absorbance of the product. Background Technology

[0002] Alpha-amylase is a classic calcium-containing enzyme that cleaves α-1,4-glycosidic bonds in starch, glycogen, and other glucose polymers to produce various polysaccharides, such as maltose and glucose. As one of the longest-used, most widely applied, and highest-yielding enzymes, α-amylase is abundant in animals, plants, and microorganisms, and has wide applications in starch processing, pasta manufacturing, ultra-high maltose syrup production, pharmaceuticals, and alcoholic beverage brewing. In brewing, α-amylase hydrolyzes starch in raw materials into sugars, accelerating starch decomposition and increasing alcohol content, thus affecting the taste and flavor of baijiu (Chinese liquor). Therefore, rapid determination of α-amylase activity is crucial for improving the quality and yield of baijiu.

[0003] According to incomplete statistics, there are currently over 200 methods for determining α-amylase. Commonly used traditional methods include viscosity / turbidity detection based on starch decomposition, the iodine starch method, and the Bernfeld reducing sugar method. However, these methods have the following problems in practical applications during the brewing process: (a) the detection steps are numerous, time-consuming, and labor-intensive, and the relevant indicators cannot be comprehensively and accurately quantified; (b) these methods are non-stoichiometric, the reaction conditions are variable, and they are often affected by endogenous substances such as glucose, making it difficult to accurately assess enzyme activity; (c) they require large amounts of samples and reagents, resulting in low flow rates and making real-time monitoring impossible. Recently, some new analytical methods have been developed, such as chromatography, fluorescence methods, colorimetry, isothermal quantitative calorimetry, and electrochemical methods. These strategies are sensitive and accurate for α-amylase detection, but require relatively expensive reagents, sophisticated instruments, and complex operating procedures. More unacceptable is that the activity of the target enzyme is easily lost in these complex processes, and the accuracy of the results cannot be guaranteed. Therefore, there is an urgent need to develop a highly sensitive and practical real-time analytical method for α-amylase activity. As is well known, cascade reactions have higher reaction efficiency than traditional sequential reactions because the active sites are closer together, the local concentration of intermediates is higher, and mass transfer is faster, thereby reducing diffusion losses.

[0004] Metal-organic frameworks (MOFs) offer a promising approach for designing multi-enzyme cascade catalytic systems. MOFs possess high specific surface area, well-defined pore structure, and tunable pore size, along with high loading capacity, providing tailored spaces for chemical reactions and facilitating the transport and transfer of internal components. Furthermore, their good biocompatibility and high stability provide excellent carriers for enzymes, effectively protecting the internal reactions. Due to these unique properties, MOFs have become promising candidate materials for constructing multi-enzyme complexes. To date, several self-assembled MOFs have been used to construct multi-enzyme complexes for biocatalytic cascade reactions. These multi-enzyme systems immobilize different enzymes within MOFs. The large distances between compartments lead to slow transport of intermediate products, thus limiting catalytic efficiency to some extent. However, the design and synthesis of these multi-enzyme complex systems require stringent conditions. Immobilizing enzymes within MOF cavities through adsorption, covalent bonding, and encapsulation overcomes the inherent drawbacks of natural enzymes, such as easy inactivation, poor stability, and high cost. However, these reported multi-complex enzyme complexes are mostly limited to single-compartment structures, with enzymes randomly distributed after encapsulation in MOF particles, thus failing to effectively control the spatial organization of different catalytic activities. Furthermore, traditional adsorption, covalent bonding, and encapsulation immobilization methods often suffer from problems such as enzyme leakage, low loading efficiency, or pore size mismatch. Therefore, seeking new strategies to design multi-compartment MOF structures is crucial. Summary of the Invention

[0005] On one hand, this invention provides a multi-enzyme nanocomposite material, wherein the multi-enzyme nanocomposite material is enzyme 1@MOF@enzyme 2@MOF; wherein enzyme 1 is glycogen debranching enzyme Ag1, enzyme 2 is glucose oxidase Gox, and MOF is MFM. The MOF is a metal-organic framework, and the MFM is a metal-organic framework containing iron and manganese ions, namely Mn-Fe-MOF.

[0006] In some embodiments, the multi-enzyme nanocomposite material appears as an elongated bipyramidal hexagonal prism shape under SEM.

[0007] In some embodiments, the MFM includes Fe 3+ and Mn 2+ In some implementations, the Fe 3+ From Fe(NO3)3·9H2O, Mn 2+ The substance is derived from Mn(Ac)2·2H2O; in some embodiments, the molar ratio of Mn(Ac)2·2H2O to Fe(NO3)3·9H2O is (7.5–9.5):(12–15.5), preferably 8:13.

[0008] On one hand, the present invention provides a method for preparing multi-enzyme nanocomposite materials, the method being as follows: preparing an MFM bimetallic solution, adding enzyme 1 solution to the bimetallic solution to form an MFM-encapsulated enzyme 1 solution, collecting product 1, adding enzyme 2 solution to the bimetallic solution to form an MFM-encapsulated enzyme 2 solution, and then adding product 1 to the MFM-encapsulated enzyme 2 solution to form a multi-enzyme nanocomposite material with multiple layers.

[0009] In some embodiments, the MFM bimetallic solution is composed of Fe 3+ and Mn 2+ It is obtained by dissolving in deionized water, wherein Fe 3 + From Fe(NO3)3·9H2O, Mn 2+ The substance is derived from Mn(Ac)2·2H2O; in some embodiments, the molar mass ratio of Mn(Ac)2·2H2O to Fe(NO3)3·9H2O is (7.5~9.5):(12~15.5); in some embodiments, the molar mass ratio of Mn(Ac)2·2H2O to Fe(NO3)3·9H2O is 8:13.

[0010] In some embodiments, the enzyme 1 solution and enzyme 2 solution are respectively composed of enzyme 1 and enzyme 2 and C. 10 H6(CO2K)2 is dissolved in deionized water to form enzyme 1, which is glycogen debranching enzyme Ag1, and enzyme 2 is glucose oxidase Gox. In some embodiments, the concentration of enzyme 1 and enzyme 2 dissolved in deionized water is 4 g / L; in some embodiments, the concentration of H6(CO2K)2 is 4 g / L. 10 The volume concentration ratio of H6(CO2K)2:Agl is 14:1; in some embodiments, the C 10 The volume concentration ratio of H6(CO2K)2 to Gox is 14:1; in some embodiments, the volume ratio of enzyme 1 solution: enzyme 2 solution: MFM bimetallic solution is 1:1:2.

[0011] In some embodiments, the preparation process further includes a stirring process; in some embodiments, the stirring speed is 500 rpm and the stirring time is 3-5 h; in some embodiments, the product collection process includes centrifugation at 8000 rpm for 10 min; in some embodiments, the product collection process further includes washing with deionized water and storing in HEPES buffer.

[0012] On the one hand, the present invention provides an application of multi-enzyme nanocomposite materials in the determination of enzyme activity.

[0013] On the one hand, the present invention provides a method for detecting enzyme activity based on multi-enzyme nanocomposite materials, comprising the following steps:

[0014] S1, mix the enzyme with starch and incubate;

[0015] S2, after adding the multi-enzyme nanocomposite material Agl@MFM@Gox@MFM, chromogenic agent and buffer, was mixed and incubated;

[0016] S3, enzyme solutions of different concentrations were obtained, and enzyme activity was detected by colorimetry.

[0017] In some embodiments, the incubation temperature is 40°C; in some embodiments, the incubation time is 15 minutes; in some embodiments, the chromogenic agent is ABTS; in some embodiments, the buffer is NaAc-HAc; in some embodiments, the enzyme concentration is 5-500 U / L, preferably 5-100 U / L.

[0018] In some embodiments, the enzyme is α-amylase.

[0019] On one hand, the present invention provides a multi-enzyme cascade system, the multi-enzyme cascade system comprising the aforementioned multi-enzyme nanocomposite material, and the multi-enzyme cascade system further comprising a chromogenic agent and a buffer solution;

[0020] Optionally, the colorimetric reagent is ABTS; optionally, the buffer solution is NaAc-HAc. Attached Figure Description

[0021] Figure 1 This outlines the preparation strategy for the multi-enzyme nanocomposite material Agl@MFM@Gox@MFM.

[0022] Figure 2 SEM characterization of the multi-enzyme nanocomposite AgL@MFM@Gox@MFM;

[0023] Figure 3 XPS characterization of the multi-enzyme nanocomposite Agl@MFM@Gox@MFM;

[0024] Figure 4 XRD characterization plots of MFM, Agl@MFM, and Agl@MFM@Gox@MFM;

[0025] Figure 5 FT-IR characterizations of Agl, Gox, Agl@MFM, and Agl@MFM@Gox@MFM;

[0026] Figure 6 The graph shows the results of the verification of the peroxidase-like activity of MFM.

[0027] Figure 7The image shows the effect of the cascade catalytic platform based on Agl@MFM@Gox@MFM.

[0028] Figure 8 This is a feasibility verification result for the cascade catalysis platform based on Agl@MFM@Gox@MFM;

[0029] Figure 9 A comparison of the thermostability of Agl@MFM@Gox@MFM and the free enzyme;

[0030] Figure 10 A comparison of the chemical stability of Agl@MFM@Gox@MFM and the free enzyme;

[0031] Figure 11 A comparison of the biological stability of Agl@MFM@Gox@MFM and the free enzyme;

[0032] Figure 12 A comparison of the storage stability of Agl@MFM@Gox@MFM and the free enzyme;

[0033] Figure 13 The graph shows the reusability test results for Agl@MFM@Gox@MFM.

[0034] Figure 14 Linear curves of α-amylase activity in the range of 5-500 U / L;

[0035] Figure 15 The image shows the results of the specific detection of α-amylase by Agl@MFM@Gox@MFM. Detailed Implementation

[0036] The following specific embodiments further illustrate the technical solution of the present invention. These specific embodiments do not represent a limitation on the scope of protection of the present invention. Non-essential modifications and adjustments made by others based on the concept of the present invention still fall within the scope of protection of the present invention.

[0037] Example 1: Preparation of the multi-enzyme nanocomposite material Agl@MFM@Gox@MFM

[0038] This embodiment provides a multi-enzyme nanocomposite material Agl@MFM@Gox@MFM, the preparation method of which is shown in the appendix. Figure 1 The specific production methods include:

[0039] (1) Preparation of AgL@MFM

[0040] Dissolve 18 mg of Mn(Ac)₂·2H₂O and 56 mg of Fe(NO₃)₃·9H₂O in 10 mL of deionized water to form a bimetallic MFM solution; dissolve 52 mg of C... 10H6(CO2K)2 and 4 mg of AgL were dissolved in 10 mL of deionized water to obtain AgL solution. Under stirring at 500 rpm, MFM solution was slowly added dropwise to AgL solution. After stirring continuously at room temperature for 3 h, the product AgL@MFM was collected by centrifugation at 8000 rpm for 10 min. The product was washed 3 times with deionized water and stored in HEPES buffer (50 mM, pH 7.4) for later use.

[0041] (2) Preparation of AgL@MFM@Gox@MFM

[0042] Dissolve 18 mg of Mn(Ac)₂·2H₂O and 56 mg of Fe(NO₃)₃·9H₂O in 10 mL of deionized water to form a bimetallic MFM solution; dissolve 52 mg of C... 10 H6(CO2K)2 and 4 mg of Gox were dissolved in 10 mL of deionized water to obtain a Gox solution. While stirring at 500 rpm, the MFM solution was slowly added dropwise to the Gox solution, and stirring continued for 5 min. Then, the synthesized Agl@MFM was slowly added dropwise. The mixture was stirred continuously at room temperature for 3 hours, centrifuged at 8000 rpm for 10 min, and the product Agl@MFM@Gox@MFM was collected. The product was washed three times with deionized water and stored in HEPES buffer (50 mM, pH 7.4) for later use.

[0043] Unless otherwise specified, the following examples are all based on the Agl@MFM@Gox@MFM prepared in this example.

[0044] Example 2 Characterization of the multi-enzyme nanocomposite material Agl@MFM@Gox@MFM

[0045] The multi-enzyme nanocomposites Agl@MFM@Gox@MFM, Agl@MFM, MFM, Agl, and Gox in this example are all from Example 1, and the characterization results are as follows:

[0046] (1) Agl@MFM@Gox@MFM was characterized by scanning electron microscopy (SEM). The SEM characterization results are as follows: Figure 2 ;

[0047] SEM images show that Agl@MFM@Gox@MFM has a bipyramidal hexagonal prism.

[0048] (2) The Agl@MFM@Gox@MFM was characterized using XPS. The XPS characterization results are as follows: Figure 3 ;

[0049] XPS images show the elemental composition of Agl@MFM@Gox@MFM. The full spectrum reveals the main characteristic peaks of C1s, N1s, O1s, Mn2p, Fe2p, S2p, and P2p. The presence of S and P elements proves that the enzyme was successfully immobilized in the MFM metal-organic framework.

[0050] (3) MFM, Agl@MFM, and Agl@MFM@Gox@MFM were characterized by X-ray diffraction (XRD). The XDR characterization results are as follows: Figure 4 ;

[0051] XDR images showed that MFM, Agl@MFM, and Agl@MFM@Gox@MFM all exhibited peaks at 15.3°, 27.0°, 31.0°, and 40.8°. The XRD results were almost identical, indicating that enzyme immobilization did not alter the crystal structure of the MFM metal-organic framework.

[0052] (4) Agl, Gox, Agl@MFM and Agl@MFM@Gox@MFM were characterized by FT-IR spectroscopy, and the FT-IR characterization results are as follows: Figure 5 ;

[0053] The FT-IR results show that:

[0054] Agl at 3446cm -1 3140cm -1 1657cm -1 and 1398cm -1 A vibration peak appears at this location;

[0055] Gox at 3444cm -1 3126cm -1 1656cm -1 and 1400cm -1 A vibration peak appears at this location;

[0056] MFM at 3443cm -1 3132cm -1 1665cm -1 1398cm -1 1294cm -1 1095cm -1 and 750cm -1 A vibration peak appears at this location;

[0057] Agl@MFM at 3437cm -1 3126cm -1 1683cm -1 1398cm-1 1294cm -1 and 748cm -1 A vibration peak appears at this location;

[0058] Agl@MFM@Gox@MFM at 3437cm -1 3126cm -1 1656cm -1 1400cm -1 1294cm -1 1185cm -1 1095cm -1 and 754cm -1 A vibration peak appears at 1656 cm⁻¹. (Agl@MFM@Gox@MFM at 1656 cm⁻¹) -1 The vibrational peak is attributed to the amide I band, proving the successful immobilization of the enzyme.

[0059] The above results collectively demonstrate that Example 1 successfully prepared the multi-enzyme nanocomposite material Agl@MFM@Gox@MFM.

[0060] Example 3: Verification of peroxidase-like activity of MFM

[0061] Using ABTS as the chromogenic substrate, the following experimental groups were designed:

[0062] ① Containing both MFM and H2O2: Mix 50 μL of MFM (0.3 mg·mL⁻¹) with H2O2. -1 The NaAc-HAc buffer (650 μL, 20 mM, pH 3.5) of ABTS (100 μL, 10 mM) and H2O2 (100 μL, 10 mM) was incubated in a shaker at 55 °C for 5 min.

[0063] ② Contains only MFM: 50 μL of MFM (0.3 mg / mL) -1 The NaAc-HAc buffer (650 μL, 20 mM, pH 3.5) and ABTS (100 μL, 10 mM) were incubated in a shaker at 55 °C for 5 min.

[0064] ③ Containing only H2O2: Incubate NaAc-HAc buffer (650 μL, 20 mM, pH 3.5) containing H2O2 (100 μL, 10 mM) and ABTS (100 μL, 10 mM) at 55 °C for 5 min in a shaker.

[0065] The absorbance of the three sets of experiments was recorded at 420 nm using a UV-Vis spectrophotometer, and the results are as follows: Figure 6As shown, it can be seen that only when MFM and H2O2 are present in the reaction system at the same time does the system exhibit a high absorbance at 420 nm, which proves the excellent peroxidase activity of MFM.

[0066] Example 4: Establishment and feasibility verification of a cascade catalytic platform for detecting α-amylase activity.

[0067] (1) Establishment of a cascade catalytic platform

[0068] like Figure 7 As shown, in the presence of α-amylase, Agl@MFM@Gox@MFM can hydrolyze starch into glucose, which is then converted into H2O2. The generated intermediate H2O2 serves as a substrate and undergoes a colorimetric reaction with ABTS triggered by MFM. Therefore, a cascade catalytic platform can be established to detect α-amylase activity.

[0069] (2) Feasibility verification

[0070] The following experimental groups were designed: ① A mixture of ABTS and Agl@MFM@Gox@MFM; ② A mixture of ABTS, Agl@MFM@Gox@MFM and starch; ③ A mixture of ABTS, Agl@MFM@Gox@MFM, starch and α-amylase; ④ A mixture of Agl@MFM@Gox@MFM and α-amylase; ⑤ A mixture of starch and α-amylase.

[0071] After incubating the above mixture at 40°C for 15 minutes, the absorbance was recorded at 420 nm using a UV-Vis spectrophotometer. The results are as follows. Figure 8 As shown, when starch and α-amylase are present simultaneously in the ABTS+Agl@MFM@Gox@MFM catalytic system, the absorbance of the reaction system is significantly enhanced, confirming the usability of the cascade catalytic platform.

[0072] Example 5: Stability determination of Agl@MFM@Gox@MFM

[0073] This embodiment tests the thermal stability, chemical stability, biological stability, and storage stability of the multi-enzyme nanocomposite material Agl@MFM@Gox@MFM. Stability is primarily measured by collecting absorbance at 420 nm. In all stability tests, the enzyme concentration was maintained at 0.3 mg / ml.

[0074] 5.1 Heat resistance stability

[0075] To investigate the heat resistance stability, the enzyme-containing solution AgL@MFM@Gox@MFM and the free enzyme AgL&Gox&HRP were placed in a water bath at 60°C for 2 hours. The enzymes were removed every 20 minutes and their activity was determined according to typical tests.

[0076] Test results are as follows Figure 9 As shown, the activity of Agl@MFM@Gox@MFM remained at 67% of its original activity after heating for 120 minutes, which is much higher than the activity of the free enzyme, proving that Agl@MFM@Gox@MFM has good thermal stability.

[0077] 5.2 Chemical stability

[0078] The chemical stability of the encapsulated enzyme system was determined by measuring the enzyme activity of the Agl@MFM@Gox@MFM system or the free enzyme Agl&Gox&HRP after incubation with 200 μL of different organic reagents for 2 h. The organic reagents used were DMF, DMSO, ethyl acetate, methanol, acetone, cyclohexane, and glutaraldehyde, and all organic reagents were prepared with buffer at a volume ratio of 1:1.

[0079] The results are as follows Figure 10 As shown, after treatment with different organic reagents for 2 hours, the multi-enzyme nanocomposite material maintained high catalytic activity, while the free enzyme had low activity, confirming the good chemical stability of Agl@MFM@Gox@MFM.

[0080] 5.3 Biological stability

[0081] The Agl@MFM@Gox@MFM system or free enzyme Agl&Gox&HRP was incubated with 200 μL of trypsin, SDS and urea at 40 °C for 2 h, and then the enzyme activity was measured according to typical tests to measure the biostability of the encapsulation system.

[0082] The results are as follows Figure 11 As shown, the multi-enzyme nanocomposite material is protected from the effects of hydrolysants and denaturants, and retains about 80% of its original activity after 120 minutes of incubation.

[0083] 5.4 Storage stability

[0084] The catalytic performance of the multi-enzyme nanocomposite material Agl@MFM@Gox@MFM and the natural enzyme Agl&Gox&HRP were tested after being placed at 4℃ for 50 days, and the storage stability of the multi-enzyme nanocomposite material was evaluated.

[0085] result Figure 12As shown, Agl@MFM@Gox@MFM retained 85% of its activity after being stored at 4°C for 50 days, while Agl, Gox, and HRP retained only 42% of their activity, demonstrating the storage stability of Agl@MFM@Gox@MFM.

[0086] Example 6: Reusability of Agl@MFM@Gox@MFM

[0087] The reusability of the Agl@MFM@Gox@MFM system was determined based on typical tests. After each test, the precipitate was centrifuged, washed with buffer, and then tested again. The tests were repeated 10 times to evaluate the reusability of the immobilized enzyme.

[0088] The results are as follows Figure 13 As shown, Agl@MFM@Gox@MFM achieved good reusability in continuous operating cycles, and the enzyme activity remained at a high level after 10 repeated cycles.

[0089] Example 7: Linear curve of α-amylase activity in the range of 5-500 U / L

[0090] In a typical reaction system, different concentrations of α-amylase (5, 10, 50, 100, 200, 400, 500 U / L, 250 μL) were incubated with starch (14.6 mM, 500 μL) at 40 °C for 15 minutes. Then, the multi-enzyme nanocomposite material Agl@MFM@Gox@MFM (0.3 mg / ml, 80 μL) and ABTS (10 mM, 200 μL) were added, and the mixture was incubated at 40 °C for another 15 minutes. The cascade catalytic performance was measured by collecting absorbance at 420 nm. In contrast, a mixture of equal amounts of free enzyme was also prepared, and error bars were obtained from three parallel experiments.

[0091] result Figure 14 As shown, the absorbance at 420 nm exhibits a good response to α-amylase, and increases linearly with α-amylase activity in the range of 5-100 U / L (R0). 2 =0.996). The limit of detection (LOD) is 2.14 U / L.

[0092] Example 8 Selectivity detection of α-amylase by Agl@MFM@Gox@MFM

[0093] To determine the selectivity of this colorimetric sensing catalytic platform, α-amylase, laccase, lipase, glucose oxidase, β-glucosidase, and horseradish peroxidase were added to a buffer containing 14.6 mM starch, incubated at 40°C for 15 minutes, and biosensing detection was performed according to typical experiments.

[0094] The results are as follows Figure 14 As shown, the prepared multi-enzyme nanocomposite material exhibits very low or even no reaction to other common enzymes, indicating that the multi-enzyme nanocomposite material has good specificity for α-amylase assay.

[0095] Example 9: Recovery Experiment of α-Amylase

[0096] Extract the yeast using PBS buffer and centrifuge before the experiment. Dilute 10-fold and add starch, incubate at 40°C for 15 minutes. Add the encapsulating enzyme system Agl@MFM@Gox@MFM (0.3 mg / ml, 80 μL) and ABTS (10 mM, 200 μL), and incubate at 40°C for 15 minutes. Collect the absorbance at 420 nm.

[0097] As shown in Table 1, the recovery rate of α-amylase in Daqu samples ranged from 97.0% to 102.7%, indicating that it has good applicability for quantifying α-amylase activity in actual fermentation samples.

[0098] Table 1. Detection results of α-amylase in actual samples.

[0099] Sample <![CDATA[Spiked(U·L -1 )]]> <![CDATA[Detected(U·L -1 )]]> Recovery (%) RSD (%) Daqu1 149.1 153.2 102.7 2.6 Daqu2 177.6 172.3 97.0 4.6 Daqu3 167.7 167.1 99.6 4.5

Claims

1. A multi-enzyme nanocomposite material, characterized in that, The multi-enzyme nanocomposite material is enzyme 1@MOF@enzyme 2@MOF; Wherein, enzyme 1 is glycogen debranching enzyme Agl, enzyme 2 is glucose oxidase Gox, and MOF is MFM.

2. The multi-enzyme nanocomposite material as described in claim 1, characterized in that, The multi-enzyme nanocomposite material appears as a slender, bipyramidal hexagonal prism shape under SEM. Preferably, the MFM comprises Fe 3+ and Mn 2+ ; Preferably, the Fe 3+ From Fe(NO3)3·9H2O, Mn 2+ From Mn(Ac)2·2H2O; Preferably, the molar ratio of Mn(Ac)2·2H2O:Fe(NO3)3·9H2O is (7.5~9.5):(12~15.5), and more preferably 8:

13.

3. A method for preparing the multi-enzyme nanocomposite material as described in any one of claims 1-2, characterized in that, To prepare an MFM bimetallic solution, enzyme 1 solution was added to the bimetallic solution to form an MFM-encapsulated enzyme 1 solution. Product 1 was collected. Enzyme 2 solution was added to the bimetallic solution to form an MFM-encapsulated enzyme 2 solution. Then, product 1 was added to the MFM-encapsulated enzyme 2 solution to form a multi-enzyme nanocomposite material.

4. The preparation method according to claim 3, characterized in that, The MFM bimetallic solution is composed of Fe 3+ and Mn 2+ It is obtained by dissolving in deionized water, wherein Fe 3+ From Fe(NO3)3·9H2O, Mn 2+ From Mn(Ac)2·2H2O; Preferably, the molar mass ratio of Mn(Ac)2·2H2O and Fe(NO3)3·9H2O is (7.5~9.5):(12~15.5); Preferably, the molar mass ratio of Mn(Ac)2·2H2O and Fe(NO3)3·9H2O is 8:13; Preferably, the enzyme 1 solution and enzyme 2 solution are prepared by reacting enzyme 1 and enzyme 2 with C, respectively. 10 H6(CO2K)2 is dissolved in deionized water to form enzyme 1, which is glycogen debranching enzyme Ag1, and enzyme 2 is glucose oxidase Gox. Preferably, the concentration of enzyme 1 and enzyme 2 dissolved in deionized water is 4 g / L; Preferably, the C 10 The volume concentration ratio of H6(CO2K)2 to Agl is 14:1; Preferably, the C 10 The volume concentration ratio of H6(CO2K)2 to Gox is 14:1; Preferably, the volume ratio of enzyme 1 solution: enzyme 2 solution: MFM bimetallic solution is 1:1:

2.

5. The preparation method according to claim 3, characterized in that, The preparation process also includes a stirring process; Preferably, the stirring speed is 500 rpm and the stirring time is 3-5 hours. Preferably, the product collection process includes centrifugation at a speed of 8000 rpm for 10 minutes; Preferably, the product collection process further includes washing with deionized water and storing in HEPES buffer.

6. The application of the multi-enzyme nanocomposite material according to any one of claims 1-2 or the multi-enzyme nanocomposite material prepared by the method according to any one of claims 3-5 in the determination of enzyme activity.

7. A method for detecting enzyme activity based on multi-enzyme nanocomposite materials, characterized in that, Includes the following steps: S1, mix the enzyme with starch and incubate; S2, after adding the multi-enzyme nanocomposite material Agl@MFM@Gox@MFM, chromogenic agent and buffer, mix and incubate; S3, enzyme solutions of different concentrations were obtained, and enzyme activity was detected by colorimetry.

8. The method as described in claim 7, characterized in that, The incubation temperature is 40°C; Preferably, the incubation time is 15 minutes; Preferably, the color developer is ABTS; Preferably, the buffer solution is NaAc-HAc; Preferably, the concentration of the enzyme is 5-500 U / L, more preferably 5-100 U / L.

9. The application / method as described in any one of claims 6-8, characterized in that, The enzyme is α-amylase.

10. A multi-enzyme cascade system, characterized in that, The multi-enzyme cascade system includes the multi-enzyme nanocomposite material according to any one of claims 1-3 or the multi-enzyme nanocomposite material prepared by the method according to any one of claims 4-6; Preferably, the multi-enzyme cascade system further includes a chromogenic agent and a buffer solution; Preferably, the color developer is ABTS; Preferably, the buffer solution is NaAc-HAc.